Intermetallic growth of Sn-Ag-Sb/Ni plated Cu in power packaging subject to thermal aging - Shualdi W.; Ahmad I.; Omar G.; Isnin A. (2023)
Intermetallic compound (IMC) growth behavior plays an important role in solder joint reliability of electronic packaging assemblies. The growth of interfacial IMC compounds and the interfacial voids/crack formation between Sn-25Ag-10Sb lead-free solders and Nickel plated Cu in power package subject to thermal aging are reported. The thicknesses of interfacial Ni-Cu-Sn IMC compounds were observed after exposed to 50, 100, 200, 400 and 800 hours aging time. The temperature for the thermal aging was kept constant at 175C. It was noted that IMC layers grew in thickness as the thermal aging time increased. The highest IMC layer thickness was observed at 800 hours thermal aging time. At 800 hours aging time, the formation of voids was obvious and base metal-rich compound was also found at certain location probably due to grain boundary diffusion effect.